THE EFFECT OF CROSS-FUNCTIONAL POTENTIAL AND FOREIGN LANGUAGE LITERACY ON THE QUALITY OF TOURISM EXPERIENCE WITH MEDIA MODERATION OF PUBLIC SERVICE INFRASTRUCTURE IN BETAWI CULTURAL VILLAGE SETU BABAKAN - Rika Mariana; Viniyati Maftuchach (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
This study analyzes the influence of cross-functional competence (X1) and foreign language literacy (X2) of service personnel on the quality of the tourist experience (Y), with public service infrastructure (Z) as a moderating variable in the Setu Babakan Betawi Cultural Village, Jakarta. This study a quantitative approach using Partial Least Squares Modeling (PLS-SEM) to analyze survey data from 100 visitor. The data obtained were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) to examine the relationships between the research variables. The results show that cross-functional competence helps personnel respond adaptively and comprehensively to tourist needs, including cultural guidance and complaint handling. Foreign language literacy improves the effectiveness of service interactions (service encounters), particularly for international tourists, through clearer and more empathetic information delivery. The implementation of these two competencies has been shown to be more optimal when supported by adequate public infrastructure, such as multilingual signage, an information center, and well-maintained public facilities. The study concludes that the quality of the cultural tourism experience is not only determined by human resource capabilities but is also strengthened by the support of public service infrastructure, which acts as a key moderator. Strengthening cross-functional competencies and foreign language literacy must go hand in hand with infrastructure improvements to ensure a more integrated, memorable, and globally competitive tourism experience at Setu Babakan.